2021
DOI: 10.1128/msystems.01018-21
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Sequencing of Multiple Soil Horizons and Sites in Close Vicinity Revealed Novel Secondary Metabolite Diversity

Abstract: This study helped uncover the biosynthesis potential of forest soils via exploration of shotgun metagenome and amplicon sequencing methods and showed that both methods are needed to expose the full microbial diversity in soil. Based on our metagenome mining results, we suggest revising the historical strategy of sampling soils from far-flung places, as we found a significant number of novel and diverse BGCs and domains even in different soils that are very close to each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…Furthermore, apart from the few metagenomic projects whose MAGs we incorporated in the first part of our analysis, there are multiple such projects publicly available, some of which have been the focus of NP studies 59 . Although the reconstruction of genomes from metagenomes remains a challenge 60 and the assembly will often miss BGCs 61 , which has indirectly prevented their comparison to the cultured bacteria in the current project, metagenomics is proving a promising source of information on NPs and their producers 7,37,48,58,59 , as made apparent in the present investigation. We expect the effect of this field on NP research to become more evident in the following years.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, apart from the few metagenomic projects whose MAGs we incorporated in the first part of our analysis, there are multiple such projects publicly available, some of which have been the focus of NP studies 59 . Although the reconstruction of genomes from metagenomes remains a challenge 60 and the assembly will often miss BGCs 61 , which has indirectly prevented their comparison to the cultured bacteria in the current project, metagenomics is proving a promising source of information on NPs and their producers 7,37,48,58,59 , as made apparent in the present investigation. We expect the effect of this field on NP research to become more evident in the following years.…”
Section: Discussionmentioning
confidence: 80%
“…It is uncertain if the V4V6 primers were under amplifying or V4V5 primers over amplifying planctomycetes . Mantri et al compared 16S amplicon sequencing and shotgun sequencing of DNA from four forest soils and found that the planctomycetes were overrepresented in the amplicons sequences by several orders of magnitude (Mantri et al, 2021), suggesting that some primers can over amplify planctomycetes . However this study used V3V4 amplicons and so cannot be directly compared to ours.…”
Section: Resultsmentioning
confidence: 99%
“…The A horizon of the soil type cambisol was sampled from the Schönbuch Forest nature reserve (close to Tübingen, Germany) in November 2016. Different metagenomic HMW DNA isolation protocols were applied for subsequent Nanopore and Illumina sequencing of the DNA as described in detail in our previous study (Mantri et al 2021). The HMW DNA used for fosmid library generation was isolated following two methods of our previous study, which are summarized in the following: a small part of the library (approx.…”
Section: Soil Sampling Isolation and Sequencing Of Metagenomic Hmw Dnamentioning
confidence: 99%
“…The lasso peptide BGC 44.1 that was detected on hybrid assembled contigs (Online Resource 3) derived from the metagenome sequencing data of our previous study (Mantri et al 2021) was used as a reference sequence to design the specific primers Cl_44_SalI_fw GTC GAC CCT CCG TCG CAG AGC TGT AT (SalI recognition site underlined) and Cl_44_SacI_rv GAG CTC AAG ATG TTC CTG ACC TGC GG (SacI recognition site underlined). Using this primer pair as well as the Q5 high-fidelity DNA polymerase kit (NEB), the lasso peptide-specific genes A, B1, B2, and C of BGC 44.1 were amplified via PCR.…”
Section: Amplification and Cloning Of A Lasso Peptide Bgc From Metage...mentioning
confidence: 99%
See 1 more Smart Citation